Keamanan Laci Berbasis Mikrokontroler dengan Sensor LDR dan RFID - Yol Putra; Cipto Prabowo; Ervan Asri (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2020)
Drawers for storing micro-sized electronic items that are usually used on campus are napolly-type drawers, which are plastic drawers, these drawers are considered ineffective because there is no notification that the drawer is open or the drawer is being opened by someone. In this case the authors designed and made the Drawer Door Security Prototype Using LDR and RFID sensors with a Microcontroller-based Sentora Platform. This system is equipped with an LDR sensor as a detector that if the drawer is opened too long then the alarm will be active until the door is closed again. RFID as a drawer door opener access. ESP8266 as a medium for sending data from the Arduino System to Sentora and using a web service to provide information to the drawer owner. If the LDR sensor detects an open drawer door for too long then ESP8266 will send information to the sentora that uses the web service as a notification. If the RFID Tag is registered, the solenoid opens. The state of the solenoid as a door lock will be displayed on the web service that the state of the solenoid has changed. From making this tool, it is expected that if there is someone who wants to break into a drawer it will be easily captured and more secure because it uses multiple layers of security